2022
DOI: 10.1002/adma.202200907
|View full text |Cite
|
Sign up to set email alerts
|

Process‐Aid Solid Engineering Triggers Delicately Modulation of Y‐Series Non‐Fullerene Acceptor for Efficient Organic Solar Cells

Abstract: considered as one of the most promising green-energy technologies. [1][2][3][4] From the past several years, with the advents of start-of-the-art Y-series non-fullerene acceptors (NFAs) (Y6, Y6-BO, BTIC-2Cl-γCF 3 , BTP-eC9, L8-BO, and so on) in terms of novel electron-deficient core, dithienothiophen[3.2-b]pyrrolobenzothiadiazole, BTP, [5][6][7][8][9][10] the recording power conversion efficiencies (PCEs) have exceeded 19% in single-junction configuration and over 20% certified PCE based on tandem solar cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
136
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 60 publications
0
136
0
Order By: Relevance
“…[11][12][13][14] It has been already reported that the use of non fullerene based semiconducting materials in photovoltaics have increased the PCE up to 18.5%. 12,15,16 Among these, small-molecule acceptors with the acceptor-donoracceptor (A-D-A) backbone architecture, similar to the widely used and rather successful small-molecule donors, have drawn interest due to their easily tunable energy levels and high device performances. Besides, conjugated small molecules have attracted much attention due to their well dened structures and hence less batch to batch variation, easy synthetic control, high mobility and open circuit voltage, high purity, versatile chemical structures and easy energy level control.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] It has been already reported that the use of non fullerene based semiconducting materials in photovoltaics have increased the PCE up to 18.5%. 12,15,16 Among these, small-molecule acceptors with the acceptor-donoracceptor (A-D-A) backbone architecture, similar to the widely used and rather successful small-molecule donors, have drawn interest due to their easily tunable energy levels and high device performances. Besides, conjugated small molecules have attracted much attention due to their well dened structures and hence less batch to batch variation, easy synthetic control, high mobility and open circuit voltage, high purity, versatile chemical structures and easy energy level control.…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells (OSCs) have received extensive attention as one of the most promising photovaltiac technologies because of their potential for solution-processed large-area production, flexible and stretchable devices, and semitransparent photovoltaic applications. The power conversion efficiencies (PCEs) of typical solution-processed bulk heterojunction OSCs have reached over 18% in many systems, which is greatly attributed to the design and synthesis of high-performance nonfullerene small molecular acceptors (SMAs) and paired electronic donors, deeper understandings of the charge dynamics, morphological control, , and device engineering. Currently, most of the high-efficiency SMA materials are fused-ring electron acceptors (FREAs), such as Y-series SMAs and ITIC families, which typically consist of a large ladder-type fused multiring core with bulky side chains and two strong electron-withdrawing end-capped units. The fused-ring core could enhance the light absorption and charge carrier mobilities of FREA because of its π-extended conjugation length and rigid coplanar structures.…”
Section: Introductionmentioning
confidence: 99%
“…S1 in the ESI †), [17][18][19][20] and the power conversion efficiencies (PCEs) of the state-of-the-art devices have surpassed 19%. 21 Comprehensive studies, including those on steady state current-voltage, 17,18,[22][23][24] spectroscopic, [25][26][27] and morphological analyses [28][29][30][31][32][33] have revealed that the utilization of a rigid p-conjugated framework and the suppression of face-to-face intermolecular arrangement are advantageous for photoinduced charge generation and isotropic charge transport. However, the utilization of such fused-ring structures has faced difficulties in scale-up synthesis and structural tunability.…”
Section: Introductionmentioning
confidence: 99%